Information transmission within federal fiscal architectures: theory and evidence - Dreher, Axel; Gehring, Kai; Kotsogiannēs, Chrēstos; Marchesi, Silvia (Oxford economic papers, 2018)
Abstract. This paper explores the role of information transmission and misaligned interests across levels of governments in explaining variation in the degree
Gesehen am 24.06.2019
Advance Access Publication Date: 11 August 2017
Keywords: 1972-2010